Evaluating reading comprehension ability through the SQ4R model - SIMBOLON, N.; MARBUN, I.; SIMANJUNTAK, E.B (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The aim of this paper was to assess the reading comprehension skills of V grade students in Indonesia using the SQ4R model (Survey, Question, Reading, Reflect, Recite, Review). A sample population consisting of 30 students was selected through purposive sampling at the SDN Medan Johor. Data was collected through observation, pre-tests, and post-test examinations. The objective was to determine how the model had influenced the abilities of the participants. The results showed that SQ4R model could be used in elementary school to motivate students and make them more active in class, as well as enhance the reading comprehension skills.RESUMEN El objetivo de este trabajo fue evaluar las habilidades de comprensión lectora de los estudiantes de V grado en Indonesia utilizando el modelo SQ4R (Encuesta, Pregunta, Lectura, Reflexión, Recitación, Revisión). Se seleccionó una muestra de población compuesta por 30 estudiantes a través de un muestreo intencional en el SDN Medan Johor. Los datos fueron recolectados a través de observaciones, pruebas previas y exámenes posteriores a la prueba. El objetivo era determinar cómo el modelo había influido en las habilidades de los participantes. Los resultados mostraron que el modelo SQ4R podría usarse en la escuela primaria para motivar a los estudiantes y hacerlos más activos en clase, así como mejorar las habilidades de comprensión de lectura.